Barbed suture and gastrointestinal surgery. A retrospective analysis - Manigrasso Michele; Velotti Nunzio; Calculli Federica; Aprea Giovanni; Di Lauro Katia; Araimo Enrico; Elmore Ugo; Vertaldi Sara; Anoldo Pietro; Musella Mario; Milone Marco; Maria Sosa Fernandez Loredana; et al. (Open Medicine, 2019)
Although minimally invasive surgery is recognized as the gold standard of many surgical procedures, laparoscopic suturing is still considered as the most difficult skill in laparoscopic surgery.